The Role of Marvelous Characters in Al-Faqih’s Novels - khattab, Arej; jadullah, Sulayman (Al-Mukhtar Journal of Social Sciences, 2025)
This study explores the role of marvelous characters in shaping the narrative events in the works of the author Al-Faqih, and how their presence enriched the narrative structure, while also investigating their origins. The research’s significance stems from offering a fresh perspective on Al-Faqih’s literary output, highlighting the marvelous world—a prominent artistic theme in his literature that has not received sufficient in-depth study. Furthermore, this research connects Al-Faqih’s work to Arab and local heritage, contributing to the revival of aspects of this tradition. The study reveals the interconnectedness of these characters: jinn are linked to sorcerers as their servants, and some Muslim jinn aid righteous saints. These characters are also connected to transformed beings, as jinn, by means of sorcerers, often transform humans into animals, while righteous saints restore the transformed to their original forms. Marvelous characters are also associated with animals; certain animals are sought as offerings for sorcerers or to expel evil spirits. Al-Faqih masterfully utilized these characters to create a marvelous narrative that evokes anxiety and confusion, transporting the reader from the familiar to the extraordinary.